HUBUNGAN ANTARA RESPON PENERIMAAN INDIVIDU DENGAN KECEMASAN PADA PASIEN GANGGUAN KARDIOVASKULER DIRUANG JANTUNG RS. DUSTIRA CIMAHI - Dedi Supriadi (Jurnal Kesehatan, 2021)
Background: The onset of a chronic illness such as heart disease in a family puts pressure on the family system and requires an adjustment of the patient and other family members. This condition also requires tremendous adaptability of the family. Psychological problems that often arise in heart disease patient is the anxiety disorders. This is caused by when an individual can begin the phases in the grieving process and enters the phase of peace or acceptance phase, then he will be able to put an end to the grieving process and cope with feelings of loss completely. But if the individual remains on one phase and not enter to the phase of acceptance, then if he has a grief/ loss it will be more difficult for him to get in to the acceptance phase. Objective: This study aims to describe and identify the relationship between the individual receiving response to the diseases with anxiety in patients with cardiovascular disorders in the cardiac ward of Dustira Cimahi Hospital. The study design used was cross sectional. The samples were taken from the respondents who were cared in hospital cardiac ward in Dustira Method: Cimahi Hospital as many as 70 people, drawn by random sampling technique. The data was collected using questionnaires completed by respondents and were statistically analyzed with α = 0.05. Analysis of data was done through two stages, namely to look at univariate frequency distributions and bivariate to see the relationship (chi square) and the magnitude of the relationship (OR). Result: Statistical tests found that the individual receiving response to the diseases with anxiety obtained the p value of 0.046. The analysis showed that there is a significant relationship between the individual receiving response to the diseases with anxiety in patients with cardiovascular disorders in the cardiac ward of the Dustira Cimahi Hospital. Recommendation: It is recommended the hospital should include the role of family members in this division of tasks, especially for the needs of clients, so that the clients can has enough rest for both physical and psychological health. In addition, the hospital also need to develop nursing training programs and seminars, or to provide the opportunity for nurses to attend training and seminars conducted by other agencies relating to the handling of anxiety in patients with cardiovascular disorders, especially non-pharmacological interventions in nursing care.